2019
DOI: 10.6018/cpd.358561
|View full text |Cite
|
Sign up to set email alerts
|

Presentación de las tareas por el profesor, necesidades psicológicas y vitalidad subjetiva en alumnos de educación física

Abstract: Tomando como base la teoría de las necesidades psicológicas básicas (Deci y Ryan, 2002), en este estudio se examinó si la percepción que tiene el alumno de la presentación de las tareas por parte del profesor predice la satisfacción de las necesidades psicológicas básicas, y éstas a su vez predicen el bienestar (vitalidad subjetiva) de los alumnos en la sesión de educación física. La muestra estuvo compuesta por 515 niños (272 hombres [M = 11.28 años; DT = .49] y 243 mujeres [M = 11.36 años; DT = .48]) estudia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 13 publications
2
9
0
10
Order By: Relevance
“…Therefore, it is particularly relevant to study the factors involved in optimal development and health in this context. In this study, and in accordance with previous studies that have found that quality in the presentation of tasks (Tristán et al, 2019) and corrective feedback are perceived as legitimate by students (Vergara-Torres et al, 2020), we consider that there may be a positive relationship between both variables, which, in turn, will have an impact on the satisfaction of psychological needs and greater perceptions of vitality in students. Taking all the above into account, the aim of this paper is to analyze a model that associates the relationships between task presentation and corrective feedback as variables associated with the teacher, and the legitimate perception of such feedback, the satisfaction of the three basic psychological needs and subjective vitality, as variables related to the students in the physical education class (see Figure 1).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Therefore, it is particularly relevant to study the factors involved in optimal development and health in this context. In this study, and in accordance with previous studies that have found that quality in the presentation of tasks (Tristán et al, 2019) and corrective feedback are perceived as legitimate by students (Vergara-Torres et al, 2020), we consider that there may be a positive relationship between both variables, which, in turn, will have an impact on the satisfaction of psychological needs and greater perceptions of vitality in students. Taking all the above into account, the aim of this paper is to analyze a model that associates the relationships between task presentation and corrective feedback as variables associated with the teacher, and the legitimate perception of such feedback, the satisfaction of the three basic psychological needs and subjective vitality, as variables related to the students in the physical education class (see Figure 1).…”
Section: Introductionsupporting
confidence: 89%
“…Quality task presentation and corrective feedback are among the most important behaviors in the instructional process in the context of physical education (Hall et al, 2011) and are variables that can be considered as predictors of pedagogical effectiveness (Hall et al, 2011;Rink, 2019). Therefore, it is important for the teacher to develop the ability to present tasks in a way that allows students to feel able to begin to engage in learning tasks (Garza-Adame et al, 2017;Tristán et al, 2019) and to provide corrective feedback that allows students to maintain a sense of confidence in improving their own mistakes. In this way, feelings of incompetence in the tasks they perform will be avoided, even though the corrective feedback contains information of poor performance (Mouratidis et al, 2010;Vergara-Torres et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Edmunds, Ntoumanis, & Duda, 2006, 2008Hagger & Chatzisarantis, 2008;Markland & Tobin, 2010;Rodrigues et al, 2018;Rodrigues et al, 2019;Rodrigues et al, 2020) e na educação física (e.g. Ntoumanis, 2001Ntoumanis, , 2005Standage, Gillison, & Treasure, 2007;Tristán et al, 2019).…”
Section: Quadro Conceptualmentioning
confidence: 99%